Marriage characteristics and reproductive health of adolescents in Turkey: findings from Demographic and Health Surveys 1998 and 2008 - Tezcan, Sabahat; Adalı, Tuğba (The Turkish Journal of Pediatrics, 2012)
Adolescent marriage is an important issue given its social and medical consequences. This study focuses on the recent trends in adolescent marriage and reproductive health in Turkey to provide insights for action. Data from the Demographic and Health Surveys of 1998 and 2008 were used. Adolescent marriage and reproductive health indicators were assessed for urban-rural residences, demographic regions and educational levels. Logistic regression was used to predict marriage and birth in adolescence. Despite the decrease in the proportion of married adolescents from 1998 to 2008, the findings suggest no improvement in some marriage characteristics. In both surveys, over 60% of ever-married adolescents had been pregnant at least once. There is an increase in contraceptive use and antenatal care. Our findings showed that in Turkey, women living in rural areas, from poor households, with more traditional parental families, with less education, and who are not working are more likely to get married in their adolescent ages.